2023
DOI: 10.35848/1347-4065/acb679
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity characteristics of a waterproof airflow sensor based on a MEMS piezoresistive cantilever and nanohole array

Abstract: This paper presents the sensitivity characteristics of a microelectromechanical systems (MEMS) piezoresistive cantilever and nanohole array used in a waterproof airflow sensor. Previously, a Pitot tube-type waterproof airflow sensor was developed for seabird biologging. Built-in MEMS piezoresistive cantilevers are used as the differential pressure sensing elements. The waterproof function is achieved using nanohole arrays via Laplace pressure. However, the mechanism underlying sensitivity reduction when nanoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, it has been suggested that a specific constant that determines the airflow rate through the cantilever and nanohole array affects the sensitivity characteristics. 22) Therefore, the attachment of waterproof films to a barometric pressure change sensor configuration may affect its characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that a specific constant that determines the airflow rate through the cantilever and nanohole array affects the sensitivity characteristics. 22) Therefore, the attachment of waterproof films to a barometric pressure change sensor configuration may affect its characteristics.…”
Section: Introductionmentioning
confidence: 99%